Skala Kebututuhan Informasi Dan Tingkat Kecemasan Pra Operasi Meningkatkan Intesitas Nyeri Pasca Bedah - Yustina Kristianingsih; Maria Elisabeth Peni t (School of Nursing, Faculty of Medicine, Lambung Mangkurat University., 2022)
Excessive preoperative anxiety can increase the occurrence of postoperative pain complications with severe intensity. The phenomenon in a private Hospital Surabaya there are still patients who tend to feel excessive fear and anxiety before surgery. The purpose of this study was to analyze the correlation between the level of anxiety preoperative patients and the pain intensity of postoperative. The study used correlation study with a cohort design with 34 respondents taken using consecutive sampling techniques. The level of preoperative anxiety was assessed using the Amsterdam Preoperative Anxiety Information Scale (APAIS) questionnaire and postoperative pain intensity was assessed using Visual Analog Scale (VAS). Statistical analysis relationship between preoperative anxiety levels and postoperative pain intensity using Spearman Rank test with p value= 0,000, and rs value +0.622. Relationship between the level of preoperative anxiety and the intensity of postoperative pain using the Spearman Rank with a value of p = 0.000, and a value of rs +0.804. Based of the results of the study management needed to give education regarding the operation patient will undergo so that it can reduce the intensity of postoperative pain and can speed up the healing process and patient care time.